La posedición en el aula de traducción jurídica: un estudio exploratorio / Post-editing in the Legal Translation Classroom: an Exploratory Study - Accogli, Francesca (HERMES - Journal of Language and Communication in Business, 2024)
This article addresses the challenges and opportunities posed by the use of machine translation (MT) and post-editing (PE) in the training of legal translators in the Spanish-Italian combination. The aim is to find out whether students who do not have specific training in MT and PE, but a sufficiently developed translation competence, are able to successfully apply the MT and PE concepts learned during a short workshop in their Specialized Translation course and, as a result, produce a satisfactory post-edited translation of acceptable quality. The results show that students have an inward critical attitude towards the use of MT, so they are not influenced by the MT output. Moreover, they have adequate skills to immediately detect not only most of the errors related to concordance and lack of logic, but also the more hidden ones that require a subsequent revision.